Analisis Wacana “Kok Bbm Naik Pak Bhabin” dalam Pendekatan Interactional Sociolinguistics - Daning Wahyu Rokhana; Bernardus Wahyudi Joko Santoso; Rustono Rustono (Balai Bahasa Sulawesi Selatan, 2023)
Humans convey their ideas through a discourse (speech), both oral and written. One form of oral speech that can be listened is a video that shown on the Youtube platform. Purposes of this study are (1) to describe how the characters build social interactions according to their social background in speech and, (2) to describe the strategies for using language and non-language elements by the characters according to their social background. This study uses an interactional sociolinguistics approach with listening, note-taking data collection methods and qualitative descriptive data analysis. Research’s object is a video entitled